Co-Delivery of Sphingosomal Formulation Containing BCL2 siRNA Doxorubicin for the Treatment of Lung Cancer - Nayak, Prashant; Charyulu, Rompicherla Narayana (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Lung cancer continues to pose a major challenge to global health, with limited therapeutic options and high mortality rates. One factor that contributes to this is the overexpression of BCL2, an anti-apoptotic protein that plays a role in tumor progression and resistance to therapy in lung cancer. To address this challenge, we investigated the potential of a co-delivery strategy using a sphingosomal formulation to simultaneously deliver BCL2 siRNA and Dox, a commonly used chemotherapy drug. Materials and Methods: The sphingosomal formulation was prepared using a combination of sphingomyelin and cholesterol, providing stability and controlled release properties. BCL2 siRNA and Dox were incorporated into the sphingosomes within the liposomal core. The formulation was characterized by size, surface charge and encapsulation efficiency. NTA analysis was performed and TEM was done to check surface morphology, MTT, SRB, apoptosis and cell cycle assay for anticancer activity. Results: The formulation SD particle size by Malvern zeta sizer was found to be 165.1 nm. In TEM results also the range was in 145-205 nm whereas NTA analysis showed the size of the SD formulation as 173.8 nm hence the particle size of the formulation is in the Nano range of 200 nm. The anti-cancer activity of SD formulation was confirmed by MTT with IC50 of 0.285 µm and SRB assay IC50 of 0.357 µm against A 549 cell lines. The formulation SD showed very significant anti-cancer activity against Dox. Apoptosis and cell cycle analysis showed the formulation SD was much better in efficacy as compared to Dox. Conclusion: The Sphingosomal formulation (SD) effectively co-delivers BCL2 siRNA and Dox, demonstrating superior anti-cancer activity against A549 cell lines compared to Dox alone. The formulation's nanoscale size and enhanced efficacy highlight its potential as a promising strategy to improve treatment outcomes and address resistance in lung cancer.
Keywords: BCL2 siRNA; Doxorubicin; TEM; Lung cancer; MTT